Clinical and genetic features of luscan-lumish syndrome associated with a novel de novo variant of SETD2 gene: Case report and literature review - Zhang, Yanqing; Zhang, Haozheng; Wu, Wei; Wang, Dong; Lv, Yuqiang; Zhao, Dongmei; Wang, Lingxiao; Liu, Yi; Zhang, Kaihui (Frontiers in Genetics, 2023)
Introduction: Luscan-Lumish syndrome (LLS) is currently recognized as a rarely-observed condition featured with overgrowth, macrocephaly, obesity, type I Chiari malformation, and linguistic retardation. So far, there have been only a few LLS cases registered worldwide, but with none of them reported from China. To acquire a deeper understanding on the clinical and genetic features of this disease, a Chinese boy with LLS caused by a heterozygous variant in SETD2 gene was investigated in the present study. Methods: The patient was clinically examined and the medical history of his family was collected. Genetic testing was performed to determine the genetic etiology. Results: The proband was a boy aged 5-year-7-month-old, who was referred to our hospital due to "being a slow learner in kindergarten". The child had a history of delayed motor and language development in comparison to his peers. After admission, physical examination revealed tall stature and macrocephaly as the major manifestation, in addition to a relatively lower rating in intelligence assessment as well as abnormal MRI images showing a slightly shorter corpus callosum accompanied by a mildly thinner corpus callosum body. Whole exome sequencing (WES) revealed a heterozygous c.2514_2516delTAG (p.Ser838del) variant in SETD2 gene, which was subsequently identified as a novel de novo variant. According to the standardized genetic variant classification published by the American College of Medical Genetics and Genomics (ACMG), the variant, with a pathogenicity analysis result indicating PS2 + PM2_Supporting + PM4, was determined to be likely pathogenic. Conclusion: LLS, not having been recognized till recent years, is identified as an autosomal dominant syndrome triggered by SETD2 gene mutation. As the first report of LLS in China, the case in our study was proved to be associated with a unique type of SETD2 gene mutation that has never been reported previously, which is believed to enrich the mutation spectrum of SETD2 gene and also, deepening the clinicians' understanding on the disease.